Political economy behind taxation of ecological energy sources in the European Union - Nikiforova, Valeriia; Brixiová, Zuzana; Klazar, Stanislav, 1974-; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2020)
This bachelor thesis focuses on the evaluation of energy taxation policies and their effect on the share of renewable energy (RE) in total energy consumption in the European Union. The Community’s harmonization of energy taxation and tax incentives are described. For the evaluation correlation, multi regression and comparative analyses were performed. Within the analysis, no relation was found between motor fuel rates and share of RE in transport, between implicit tax rate for energy products and overall share of RE in total energy consumption, and between revenues form energy taxes (as % of GDP) and overall share of renewable energy in total energy consumption.
Vedoucí práce: Zuzana Brixiová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: zdanění a daňová politika [obor bakal. práce]; bakalářské práce; bachelor's theses